2013
DOI: 10.1021/jo400975t
|View full text |Cite
|
Sign up to set email alerts
|

A Radical Cascade Cyclization To Prepare Dihydrothiophenes Induced by Thiyl Radicals as Sulfur Biradical Equivalents

Abstract: Bicyclic dihydrothiophenes are readily prepared by a radical cascade cyclization reaction triggered by the addition of a thiyl radical under thermal or photoirradiation conditions. The translocated radical attacks the sulfur atom in the initial radical donor unit in an SHi manner. Sufficient stereoselectivity is achieved when a large excess of disulfide is used for the reaction under photoirradiation conditions. The reaction in the absence of solvents provides vinylsulfides instead of dihydrothiophenes. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…115 The Nomoto and Ogawa group introduced a binary diphenyl disulfide (PhS) 2 and tetraphenyldiphosphine (Ph 2 P) 2 system for thiophosphination of an yne-ene for the synthesis of functionalized five-member ring product 134 (Scheme 62). 116…”
Section: Reactions Of Sulfenyl Radicals With Yne-enes and Diynesmentioning
confidence: 99%
“…115 The Nomoto and Ogawa group introduced a binary diphenyl disulfide (PhS) 2 and tetraphenyldiphosphine (Ph 2 P) 2 system for thiophosphination of an yne-ene for the synthesis of functionalized five-member ring product 134 (Scheme 62). 116…”
Section: Reactions Of Sulfenyl Radicals With Yne-enes and Diynesmentioning
confidence: 99%
“…It is known that dialkyl disulfides and diaryl disulfides can undergo homolytic fission to generate thiyl radicals via irradiation with approximately 300–350 nm UV light. , Figure shows the mechanism for the formation of compound 4 via a disulfide–yne reaction. Photoirradiation of dimethyl disulfide produces methylthiyl radicals [ A ], which add to the CC bond to generate vinyl radicals [ B ] and [ B′ ].…”
Section: Resultsmentioning
confidence: 99%
“…Stereochemistry of stannolane 2b and 2c was determined by NMR analyses. Firstly, we thought that all of the configuration of compound 2 except for that on the tin atom must be 3S,3aS as illustrated in Scheme because the cascade reaction always progresses in a highly stereoselective manner [5], [6] [9]. In the previous results, we found that an alkyl group on tin atom shows downfield shift if the group located in the cis ‐position to the ester group at the bridgehead carbon.…”
Section: Resultsmentioning
confidence: 99%